Las circunscripciones especiales: ¿unas instituciones obsoletas? (2011)
The article is based on a double empirical finding: firstly, special constituencies make the colombian electoral process in general increasingly difficult to understand for voters and hard to manage for the authorities. Secondly, the results they get do not help indigenous and afrocolombian social movements as they are supposed to do, especially since the political reform of 2003. The paper discusses the reasons for this situation and proposes a debate on it. The author considers that if the mechanisms of positive discrimination are correctly adapted, the indigenous and afrocolombian movements would gain competing in national constituency within the framework of a single party for each one, in which internal differences would be resolved by preferential vote. In this way, if they leave the special constituencies, these minorities could benefit political reform rather than suffer its effects, which is what happens now. This would not only improve their political representations, but also allows them to consolidate as movements towards public opinion.